2019
DOI: 10.1186/s12979-019-0165-8
|View full text |Cite
|
Sign up to set email alerts
|

Age related human T cell subset evolution and senescence

Abstract: T cells are fundamental effector cells against viruses and cancers that can be divided into different subsets based on their long-term immune protection and immediate immune response effects. The percentage and absolute number of these subsets change with ageing, which leads to a reduced immune response in older individuals. Stem cell memory T cells (TSCM) represent a small population of memory T cells with enhanced proliferation and differentiation properties that are endowed with high potential for maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
123
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 26 publications
28
123
1
Order By: Relevance
“…meaning an increase of T cell memory numbers with frailty, instead of a lower number. It is known that the balance between naïve and memory T cells in peripheral blood changes with advancing age, mainly due to a decline in numbers of naïve (CD8 + ) T cells [11,55,56], which was also observed in our study (data not shown). Only few studies reported relationships between T cell populations and frailty and, to our knowledge, no associations were reported with late differentiated CD4 + TemRA T cells.…”
Section: Discussionsupporting
confidence: 85%
“…meaning an increase of T cell memory numbers with frailty, instead of a lower number. It is known that the balance between naïve and memory T cells in peripheral blood changes with advancing age, mainly due to a decline in numbers of naïve (CD8 + ) T cells [11,55,56], which was also observed in our study (data not shown). Only few studies reported relationships between T cell populations and frailty and, to our knowledge, no associations were reported with late differentiated CD4 + TemRA T cells.…”
Section: Discussionsupporting
confidence: 85%
“…We also found reduced expression of the receptor for CXCL9/10/11 (CXCR3), the apoptosis-inducing factor GZMB secreted by NK and T cells, and the effector T-cell marker (CD8A). These data suggest that age-related T-cell and NK cell dysfunction [32,33] may play a role in SARS--CoV-2 pathogenesis in older individuals.…”
Section: Factors Affecting T-cell Trafficking Are Reduced In Older Admentioning
confidence: 73%
“…The odds ratio analysis showed that healthcare workers with current illness were more susceptible to LTBI (OR=3. 39 Table 2)…”
Section: Resultsmentioning
confidence: 99%
“…38 One of the indicators is the changes in the characteristics of the T cells that are very instrumental in resisting attacks from exogenous microorganisms such as viruses and bacteria. 39 This situation will affect increasing susceptibility to various diseases, especially infectious diseases, including TB infections.…”
Section: Discussionmentioning
confidence: 99%